Mastering audio : the art and the science. - Katz, Bob, ....- (Amsterdam : Focal, 2007)
Written by an award winning, highly respected professional, Mastering Audio gives you a thorough introduction to the unique procedures and technical issues involved in mastering. Leading-edge audio concepts are explained in an easy-to-grasp holistic style. Suitable for all levels of students and professionals, it is ideal for anyone who wants to increase their mastery of digital and analog audio: musicians, producers, A&R, mastering, recording and mixing engineers.
Keywords: Geluidsopname; Geluidsweergave